NEW ELEMENTS OF SUPERCONDUCTING ELECTRONICS AND SPINTRONICS - S. L. Prischepa (Doklady Belorusskogo gosudarstvennogo universiteta informatiki i radioèlektroniki, 2019)
The basic results of development and research of new elements of superconducting electronics on the base of porous templates and superconductor - ferromagnet heterostructures are presented shortly. The fundamental aspects of original achievements in the region of the superconducting nanoelectronics, quantum physics interpretation processes in nanoscale self-assembled superconducting nanowires, the coexistence of superconductivity and magnetism are reviewed.